2010
DOI: 10.1002/clc.20746
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine and the Heart

Abstract: The use of cocaine may be associated with either acute or chronic toxicity, and approximately 5% to 10% of emergency department visits in the United States are believed to be secondary to cocaine usage. Chest pain is the most common cocaine‐related medical problem, leading to the evaluation of approximately 64 000 patients annually for possible myocardial infarction, of which approximately 57% are admitted to the hospital, resulting in an annual cost greater than $83 million. There is a plethora of cocaine‐rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 36 publications
3
87
0
5
Order By: Relevance
“…Desde el punto de vista clínico, los usuarios crónicos de cocaína exhiben un mayor riesgo de angina de pecho, infarto agudo del miocardio, muerte súbita de origen cardíaco y accidentes vasculares cerebrales 6,7 .…”
Section: Discussionunclassified
“…Desde el punto de vista clínico, los usuarios crónicos de cocaína exhiben un mayor riesgo de angina de pecho, infarto agudo del miocardio, muerte súbita de origen cardíaco y accidentes vasculares cerebrales 6,7 .…”
Section: Discussionunclassified
“…Cocaine is associated with multiple cardiovascular complications including chest pain, myocardial ischemia/infarction, arrhythmias, aortic dissection, and stroke [20]. Felker et al, 7 reported cocaine use as a rare cause of cardiomyopathy, with 10 cases found among 1278 cases of dilated cardiomyopathy at Johns Hopkins Hospital [21].…”
Section: Cocaine Cardiomyopathymentioning
confidence: 99%
“…Cocaine cardiomyopathy presents suddenly without a long prodrome. The electrocardiogram tends to show sinus tachycardia with frequent arrhythmias, including atrial fibrillation and ventricular tachycardia [20]. Echocardiogram demonstrates increased left ventricular mass and dysfunction.…”
Section: Cocaine Cardiomyopathymentioning
confidence: 99%
“…Cocaine [ (Jentzen, 1989) reviewed in (Maraj et al, 2010)], virus induced, autoimmune (possibly due to resolved microbial infection), and even vaccine induced myocarditis (Cassimatis et al, 2004) have all been reported with a wide degree of occurrence. Though very rare, the vaccine induced aetiology is classified as idiopathic due to the poorly understood mechanism of inflammation.…”
Section: Myocarditis Etiologiesmentioning
confidence: 99%